Effect of a program of primary health attention on family functionality from grandparents and grandchildren in the municipality of Guapi - Cauca - Velásquez G, Vilma Florisa; Barreto, Yenny (Universidad y Salud, 2016)
Objective: To determine the effect of a Primary Health Attention program on family functionality from grandparents and grandchildren in the municipality of Guapi in the department of Cauca. Materials and methods: A quasiexperimental study without control group was performed where 50 Afro-Colombian families participated. The program was built with the community by using culturally adapted care actions and healthy environments. The information was collected with the scale of Effectiveness of Family Functioning (ASF-20), and it was processed and analyzed with descriptive methods and range test signed of Wilcoxon. Results: The PHC program obtained a statistically significant effect on the functionality of families from grandchildren (Value-p <0,001) and grandparents (Value-p <0,004). Conclusions: The PHC program with strategy of healthy environments and culturally congruent care has effect over effectiveness of family functionality in grandparents and grandchildren in Afro-Colombian families in the municipality of Guapi, Cauca. It favored family functionality actions for the promotion of health through strategic alliances and opportunities for individual and collective development of children and grandparents.